Instrumento de medición sobre conocimientos, actitudes y prácticas en el diagnóstico cefalométrico de ortodoncistas graduados. (2022)
Measurement is defined as the process of assigning values to certain events of reality, it is an essential component in scientific research including dentistry (Arcos, 2018). The aim of this study was to design an instrument to assess the knowledge, attitudes and practices of cephalometric management, by already graduated orthodontic specialists. An initial survey was created with 103 questions with binomial response option oriented to evaluate knowledge, attitudes and practices on cephalometric management in the practice of the orthodontic specialty